2012
DOI: 10.1177/1062860612459881
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Validated Checklist for Thoracentesis

Abstract: Thoracentesis is an invasive procedure known to result in complications. Procedure skills should be taught and evaluated more effectively to improve health care quality. Validated checklists are central to teaching and assessing procedural skills. The results of the first step of the validation of a thoracentesis checklist are described. A comprehensive literature review of articles published on thoracentesis did not yield a validated checklist. A modified Delphi technique, involving a panel of 8 interdiscipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 17 publications
(19 reference statements)
0
21
0
1
Order By: Relevance
“…Five studies were identified [13, 16, 21-23]. All studies provided assessment tools for assessing competence in thoracentesis, though three of them focused on needle thoracentesis [13, 21, 22]. Two studies provided assessment tools for TPCT, but they used the Seldinger technique when inserting the catheter [16, 23].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies were identified [13, 16, 21-23]. All studies provided assessment tools for assessing competence in thoracentesis, though three of them focused on needle thoracentesis [13, 21, 22]. Two studies provided assessment tools for TPCT, but they used the Seldinger technique when inserting the catheter [16, 23].…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a PubMed search on following keywords “simulation,” “thoracentesis,” “training,” “assessment tool,” “validation,” and “chest tube” including English language papers from the last 5 years. Five studies were identified [13, 16, 21-23]. All studies provided assessment tools for assessing competence in thoracentesis, though three of them focused on needle thoracentesis [13, 21, 22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified Delphi method, explained in more detail in a previous publication, 18 was used to develop the adult LP checklist. A preliminary 20-item LP checklist was developed by 2 of the authors (DB and KB) based on their experience with teaching and performing LP (Table 1).…”
Section: Checklist Development and Delphi Roundsmentioning
confidence: 99%
“…Two articles included a published checklist as mentioned in the introduction. 12,13 Checklist Development and Delphi Rounds A modified Delphi method, explained in more detail in a previous publication, 14 was used to develop the paracentesis checklist. A preliminary 23-item paracentesis checklist was developed by 2 of the authors (DB and KB) based on their experience with teaching and performing paracentesis (Table 1).…”
Section: Review Of the Literaturementioning
confidence: 99%